# P implies Q

P => Q is only FALSE when the Premise(p) is TRUE AND Consequence(Q) is FALSE.
P => Q is always TRUE when the Premise(P) is FALSE OR the Consequence(Q) is TRUE.

P IMPLIES Q can be formulated in the following ways:

1. If P then Q
2. P only if Q
3. P is a sufficient condition for Q
4. Q is a necessary condition for P
5. Q if P
6. Q follows P
7. Q provided P
8. Q is a logical consequence of P
9. Q whenever P

P = It is raining

Q = I get wet.

P => Q

1. IF it is raining THEN I get wet
2. I get wet ONLY IF it is raining
3. It is raining IS A SUFFICIENT CONDITION FOR it is raining
4. I get wet IS A NECESSARY CONDITION FOR it is raining
5. I get wet IF it is raining
6. I get wet FOLLOWS it is raining
7. I get wet PROVIDED it is raining
8. I get wet IS A LOGICAL CONSEQUENCE OF it is raining
9. I get wet WHENEVER it is raining

The Premise(P) and the Consequence(Q) need not be related. The interpretation of the truth table depends on the formulation P and Q.

For example.

If the Moon is made of Cheese, then, the frog is blue.

The statement: The Moon is made of Cheese, and

The statement: The frog is blue.

are in no way related to each other, but nevertheless the truth table for P=>Q is valid. We would have to come up with a very magical Universe and a world for these two statements to be related and for them to make sense. That is just a question of imagination and interpretation not  question of whether the true table is correct or not.

Even if we took these two statements for our world, then would both be false so:

False => False

So looking at the truth table where P is false and Q is false we see that P => Q is True.

So, If the The Moon is made of Cheese then the frog will be blue.

Usually, however P and Q will be related and everything will make sense.

Ambiguity

The implies operator is ambigous so you need to use parenthesis when using it.

For example P => Q => R is ambigous. Does it mean (P=>Q) => R) or (P=>(Q => R))?

Here the truth table to show that they are not the same.

Logical Identity

(p=>q) <=> (not p v q)

1. Pingback: Implication « Jasoninclass's Blog

2. It seems to me that example 2 under p->q (p = it is raining and q = I get wet) is backwards. I think it should be “It is raining only if I get wet.”

• Nope Bill, sorry… it’s correct. It just sounds strange.

When P implies Q is true, then according to the truth table….
P is true only is if Q is true.

so … I get wet (P), only if, it is raining (Q).

• You stated that:

“so … I get wet (P), only if, it is raining (Q).”

but in the example, you’d originally defined P = it is raining
and Q = I get wet ..it appears as though you transposed P and Q..typeo?

3. The truth tables were helpful. I still would like to better conceptualize the fact that p=>q is logically equivalent to not p or q.

4. And, actually, I do think that #2 is wrong. Under p=>q, you could get wet if it’s raining or not. BUT if it is raining, then you surely get wet.

5. Does negation of p implies q is ~p implies ~q ? If not then what is correct answer ? Reply me back soon….its urgent